IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS KASIH SAYANG DALAM MENINGKATKAN DISIPLIN SISWA KELAS 5 DI SDN PASAWAHAN KIDUL - virgo, Agus; Kaniati, Nia; Maylani, Fitriyah; Nurmalasari, Iis; Warta, Waska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the implementation of character education based on compassion in improving the discipline of fifth-grade students at SDN Pasawahan Kidul. The research employed a qualitative descriptive approach with a single case study design. Data were collected through in-depth interviews, observation, and documentation, and analyzed interactively through data reduction, presentation, and conclusion drawing. The findings show that teachers have a good understanding of the concept of compassion as an approach that emphasizes empathy, respect for individual differences, and patient guidance. The strategies implemented include role modeling, habituation of positive values, respectful communication, and involving students in formulating class rules to foster a sense of belonging and responsibility. Students responded positively, showing increased openness, confidence, and awareness in adhering to school rules. The students’ disciplinary behavior improved significantly in punctuality, compliance, task responsibility, and courteous attitudes. Challenges encountered include limited time, diverse student characteristics, and inconsistent family support. Nonetheless, the compassionate approach effectively fostered internal discipline in students in a meaningful and sustainable way. Therefore, compassion-based character education is relevant to be developed more widely in elementary schools as it aligns with moral development theories and Indonesian cultural values of care and togetherness. Keywords: Character education, compassion-based approach, discipline, elementary school, moral development